2016
DOI: 10.15761/god.1000155
|View full text |Cite
|
Sign up to set email alerts
|

Granular cell tumor (Abrikossoff's tumor) of the labium majus: a case report

Abstract: Granular Cell Tumor (GCT) is an uncommon, benign tumor of neural origin resembling Schwann cells. It is more common in females and blacks. Head and neck regions are the most sites involved by the tumor, but it can occur in any part of the body. Vulva, ovary and cervix in females and scrotum in males can present GCT. The importance of this tumor is potential malignant transformation in rarity. Total excision is the choice treatment for GCT because of probability of recurrences.In this article, we described a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…GCT was first described in 1926 by Abrikossoff [5], who called these tumors "granular cell myoblastomas, " suggesting that their origin was from skeletal muscle. Additional studies have demonstrated their close association with peripheral nerves [4]. Later, the use of electron microscopy and immunohistochemical techniques provided further evidence supporting the differentiation of Schwann cells from these tumors, which later became known as GCT.…”
Section: Case Presentationmentioning
confidence: 92%
“…GCT was first described in 1926 by Abrikossoff [5], who called these tumors "granular cell myoblastomas, " suggesting that their origin was from skeletal muscle. Additional studies have demonstrated their close association with peripheral nerves [4]. Later, the use of electron microscopy and immunohistochemical techniques provided further evidence supporting the differentiation of Schwann cells from these tumors, which later became known as GCT.…”
Section: Case Presentationmentioning
confidence: 92%